Influencia del gas natural como combustible de los medios de transporte vehicular en el medio ambiente de la ciudad de Lima - Parrera Espinoza, Segundo Albertano (2010)
The present investigation work, shows the influence of the natural gas as vehicular fuel in the environment of the city of Lima. The technique of the monitoreo has been used that is governed under the limits of the environmental authorities according to the necessities (Protocol of monitoreo of the quality of the air and administration of the data). The obtained results have been carried out under the inspection of the Program of Surveillance of the quality of the air in Lima and Callao, through five fixed stations of monitoreo. It is presented the Charts of the present pollutants in the air, taken in the Callao, south Lima, north Lima, Lima this and Lima city. At the same time, it is presented the monthly concentration variations of the years 2008 and 2009 and the annual concentrations from the year 2000 until the year 2009. An analysis of results is made to study its behavior and its tendencies in the time, considering the National Standards of annual Environmental Quality, (ECA) and the values of the World Organization of the Health (OMS). For that that, starting from the year 2006 a change is observed in the tendencies of the gassy pollutants, but that it still persists the material particulado; being clear the influence of the natural gas, and in consequence to propose the solution alternatives.